Pengaruh Role Of Conflict Dan Role Of Ambiquity Terhadap Kepuasan Kerja Dan Komitmen Organisasional Perawat RSUD Bagas Waras Klaten - Ndari, Ika Wulan, Prof.Dr. M. Wahyuddin, M.S, Drs. M. Farid Wajdi, M.M., Ph.D (2017)
This research aims to examine the influence of role conflict and role of ambiquity to the job satisfaction and organizational commitment. The population of this research wass all nurse's of the RSUD Bagas Waras Klaten. Analysis techniques used path analysis and SPSS software version 20. The results showed that: the role of conflict and the role of ambiquity significant and negative influence on job satisfaction; the role of conflict and the role of ambiquity significant and negative influence on organizational commitment; job satisfaction significant and positive influence on organizational commitment; job satisfaction mediates influence of role of conflict and the role of ambiquity against on organizational commitment.